2009
DOI: 10.1007/s10493-009-9303-x
|View full text |Cite
|
Sign up to set email alerts
|

Life cycle and behaviour of the predaceous mite Cunaxatricha tarsospinosa (Acari: Prostigmata: Cunaxidae)

Abstract: Life cycle and behaviour of Cunaxatricha tarsospinosa Castro & Den Heyer from rubber trees in Brazil were studied, with Tenuipalpus heveae Baker offered as prey.The study was conducted at 25.4 +/- 0.2 degree C, 83 +/- 5% RH and 12:12 h L:D photophase. The egg stage was the longest immature stage, lasting 17.1 +/- 1.3 days (mean +/- SE); total juvenile development was completed in 33.2 +/- 2.8 days. Lifetime fecundity was 12.0 +/- 2.2 eggs. Intrinsic rate of population increase was low, suggesting that T. hevea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 23 publications
(21 reference statements)
2
14
0
Order By: Relevance
“…Trichobothrium is often present on tibia IV (except in Cunaxatricha Castro and Den Heyer), smooth, as in Coleoscirinae and Cunaxiinae, or setose, as in Bonziinae. Cunaxid eggs may be highly ornamented with reticulate sheaths or spines (Krantz and Walter 2009 ) and often covered by a webbing, that may be absent as reported by Castro and Moraes ( 2010 ) for Cunaxatricha tarsospinosa Castro and Den Heyer for eggs laid on tree branches.…”
Section: Cunaxidaementioning
confidence: 95%
See 1 more Smart Citation
“…Trichobothrium is often present on tibia IV (except in Cunaxatricha Castro and Den Heyer), smooth, as in Coleoscirinae and Cunaxiinae, or setose, as in Bonziinae. Cunaxid eggs may be highly ornamented with reticulate sheaths or spines (Krantz and Walter 2009 ) and often covered by a webbing, that may be absent as reported by Castro and Moraes ( 2010 ) for Cunaxatricha tarsospinosa Castro and Den Heyer for eggs laid on tree branches.…”
Section: Cunaxidaementioning
confidence: 95%
“…Bioecological information about cunaxids was published by the following authors: Schruft ( 1971 ), Soliman et al ( 1975 ), Zaher et al ( 1975 ), Taha et al ( 1988 ), Walter and Kaplan ( 1991 ), Walter et al ( 1993 ), Sathiamma ( 1995 ), Arbabi and Singh ( 2000 ) and Castro and Moraes ( 2010 ). Those studies have shown the ability of cunaxids to prey upon Eriophyoidea and Tetranychoidea, as well as upon other small arthropods and nematodes.…”
Section: Bioecologymentioning
confidence: 99%
“…All cunaxids are thought to be opportunistic predators, though an undescribed Rubroscirus was observed to drink drops of honeydew in addition to feeding on live prey (Walter and Proctor 1999). Cunaxids have been reported to feed on active prey such as Collembola (Sellnick 1926, Heryford 1965), bark lice (Zaher et al 1975a), and thrips (Milne 1977), and relatively inactive prey such as scales (Ewing and Webster 1912, Gerson 1971), nematodes (Taha et al 1988, Walter and Kaplan1991), phytophagous mites (Meyer and Ryke 1959, Zaher et al 1975a, Den Heyer and Ryke 1970, Taha et al 1988, Smiley 1992, Sathiamma 1995, Arbabi and Singh 2000, Ferla 2001, Lahiri et al 2004, Castro and Moraes 2010), and paratydeid mites (pers. obs.).…”
Section: Introductionmentioning
confidence: 99%
“…Within Cunaxinae, for instance, Armascirus and Dactyloscirus wait, sometimes for hours, to ambush prey (Walter and Proctor 1999), whereas Allocunaxa actively search for prey (Castro and Moraes 2010). …”
Section: Introductionmentioning
confidence: 99%
“…Cunaxa capreolus (Berlese)] and rootknot nematodes [i.e. Coleoscirus simplex (Ewing)] (Zaher et al 1975;Walter and Kaplan 1991;Castro and Moraes 2010).…”
Section: Introductionmentioning
confidence: 99%